What makes you "super-rich"? New evidence from an analysis of football players' earnings - Vincenzo Carrieri; Francesco Principe; Michele Raitano (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
This article investigates the influence of performance, popularity and power on "superearnings" using a unique panel dataset of Italian football players built on various sources of data. Using OLS, Panel and Unconditional Quantile regression techniques, we find that detailed measures of these factors are all significantly associated with higher wages. Popularity dominates all the other factors at the right tail of earnings distribution and the agent's power contributes mostly to allocate players in richer teams. These new findings challenge the interpretations of super-earnings based only on very talented workers who "win and take all". – – Dieser Beitrag untersucht den Einfluss von Leistung, Popularität und Macht auf "Super-Verdienste" mithilfe eines Paneldatensatzes von italienischen Fußballspielern, der auf verschiedenen Datenquellen beruht. Anhand von OLS, Panel- und "Unconditional Quantile regression"-Techniken zeigt sich, dass diese Faktoren alle signifikant mit höheren Löhnen assoziiert sind. Der Faktor Popularität wirkt sich am stärksten auf das rechte Ende der Einkommensverteilung aus, die Macht des Spielerberaters vor allem auf die Zuteilung der Spieler in wohlhabende Teams. Diese neuen Erkenntnisse stellen die Annahme in Frage, dass "Super-Verdienste" nur von sehr talentierten Spielern erzielt werden, die "alles gewinnen und bekommen".
Keywords: J31; L83; J24; C23; D31; 330; superstars; top incomes; football players' earnings; panel data; unconditional quantile regressions